Manajemen Kelas dalam Meningkatkan Kedisiplinan Siswa MI AL-MANAR - Dewi, Aura Chantika; Ramadhan, Afiif; Faqih, Izzat Abdullah; Permana, Hinggil (Jurnal Inovasi dan Teknologi Pendidikan, 2025)
This study aims to determine and analyze the discipline of MI AL-MANAR school which is a conscious form of realizing the learning process so that students can actively improve their potential to have a religious spiritual basis, control, muia morals, good personality, and skills. This research was conducted at MI AL-MANAR and used a qualitative method that uses a descriptive analysis approach, which is research that focuses on an in-depth understanding of the phenomena experienced by the research subject, including various aspects such as behavior, perception, motivation, and action. The data obtained is then described in detail through language-based qualitative analysis, as well as by conducting interviews with the vice principal and teachers concerned. The results in this study indicate that good classroom management is very influential in improving student discipline. There are several approaches applied by the school in creating an orderly and productive learning atmosphere including, among others, a managerial approach, a class management regulation approach, a behavioral approach and inhibiting factors to student discipline. All of these approaches can have a major influence on the continuity of teaching and learning activities at MI AL-MANAR.